Visualization of the leakage of pancreatic juice using a chymotrypsin‐activated fluorescent probe. Issue 9 (13th June 2013) - Yamashita, S.; Sakabe, M.; Ishizawa, T.; Hasegawa, K.; Urano, Y.; Kokudo, N.
Abstract : Background: Pancreatic fistula (PF) remains the most serious complication after digestive surgery. It is difficult to prevent because of the inability to visualize the leakage of pancreatic juice during surgery or to evaluate the protease activity of leaked fluid, which is responsible for PF formation. Methods: The fluorescence intensities of a chymotrypsin probe (glutamyl‐phenylalanine hydroxymethyl rhodamine green with added trypsin) in pancreatic juice and in intestinal or abdominal fluids drained after pancreatic resection were evaluated. The chymotrypsin probe was sprayed on to filter papers that had been placed on the resected pancreatic stump in patients undergoing pancreaticoduodenectomy or central pancreatectomy. The ability of this technique to visualize the leakage of pancreatic juice and predict postoperative PF formation was assessed. Results: The fluorescence intensity of the chymotrypsin probe in 76 fluid samples correlated positively with amylase levels ( r s  = 0·678, P  < 0·001). The fluorescence patterns of the pancreatic stump were classified grossly into the three types: duct (fluorescence signal visualized only on the stump of the main pancreatic duct, 16 patients), diffuse (ductal stump and surrounding pancreatic parenchyma, 7) and negative (no fluorescence signal, 7). Symptomatic PFs developed in 13 of 23 patients with duct‐ or diffuse‐type fluorescence, but in none of the seven patients with negative‐type fluorescence ( P  = 0·008). Conclusion: The chymotrypsin probe enabled determination of the protease activity in drained pancreatic fluid samples and allowed real‐time visualization of pancreatic juice leakage during surgery. Abstract : New technique to diagnose pancreatic fistula